Treatment of refractory lupus nephritis using leflunomide: A prospective study - Zhang, Shuo; Chen, Yiran; Chen, Xin; Zhao, Yan; Zeng, Xiaofeng; Zhang, Fengchun; Wang, Li; Li, Mengtao (Frontiers in Immunology, 2023)
Introduction The condition of refractory lupus nephritis (LN) negatively affects the prognosis and life expectancy of the patients, posing a challenge to manage in clinical. This interventional study evaluated the efficacy as well as safety of leflunomide in patients with refractory LN. Methods Twenty patients with refractory LN were enrolled in this study. A daily dose of 20–40 mg of leflunomide was given to the patients orally. Meanwhile, immunosuppressives were withdrawn, and corticosteroids were gradually tapered. There was an average follow-up period of 3, 6, and 12 months for most patients while some were observed for as long as 24 months. We recorded biochemical parameters and side effects. We calculated the response rate using intention-to-treat analysis. Results Eighteen patients (90%) completed the study. At 3 months, 80% (16/20) of the patients achieved more than a 25% decrease in 24-hour urine protein quantity. At 6 months, three patients (15%) achieved a partial response, and five patients (25%) achieved a complete response. However, by 12 months and 24 months, the complete response rate dropped to 15% and 20%, respectively. The objective responses were 30% (6/20), 40% (8/20), 40% (8/20), and 30% (6/20) at 3, 6, 12, and 24 months, respectively. Two patients withdrew from the study due to developing cytopenia and leucopenia. Conclusion In patients diagnosed with refractory LN, our study shows that leflunomide could be a promising treatment option owing to its response rate and safety profile.